Trends and practices in the integration of manufacturing and the Internet - Jianrong TAN (物联网学报)
Based on the in-depth study of the technical connotation of the integration of manufacturing industry and Internet,the technical bottleneck of the integration was put forward from four perspectives of the concept,method,goal and achievement of the deep integration.In view of different fields,ten key technologies of deep integration of manufacturing industry and Internet were analyzed in detail.And the different scenarios of key technology application were given.